A Visual Language for Animating Sketches - DAVIS, Richard C. (Institutional Knowledge at Singapore Management University, 2004)
We present our research into visual languages for animating sketches. Animation is a rich mode of communication that is currently accessible to few. Simple animation systems exist, but severely restrict the types of motion that can be represented. Our field studies are demonstrating that would-be animators need to coordinate many objects moving in a variety of ways. The visual language described here allows a variety of motions to be defined with hand gestures, and gives visual feedback for coordination of events. This may open up computerized communication to users who think in dynamic visual images.